An Islamic approach to the theory of the firm : the views of Malaysian managers - Mhd. Sarif, Suhaimi; Ismail, Yusof (2013)
The conventional approach to the theory of the firm has not been adequate to respond to external, internal, and human dynamism. The market-based theory of the firm emphasises on the industrial organizational perspective only of the firm, which is lack of dynamism. The evolutionary approach into resource-based and knowledge-based of theory of the firm is also unable to provide a satisfactory theory of the firm due to lacks of spirituality foundation to sustain intellectual contribution from knowledge workers. Thus, this study explores an Islamic approach, which is based on Tawhidic paradigm to the theory of the firm as a mean to achieve organizational sustainable innovation and competitive advantage. The study obtained views through personal interview with 10 managers from companies that practice Islamic management system. The informants argued that the current practice emphasized on profit maximization and competitive advantage at the cost of human spirituality development.